Von Hippel-Lindau disease with extramedullary and pancreatic involvement - Pantigozo-Rimachi, Andrea (2020)
We report a patient with Von Hippel-Lindau disease who presented with an intradural extramedullary hemangioblastoma as a primary manifestation.